1988
DOI: 10.1111/j.1365-2559.1988.tb02042.x
|View full text |Cite
|
Sign up to set email alerts
|

Collagenous colitis: an electron microscopic study including comparison with the chronic fibrotic stage of ulcerative colitis

Abstract: Light and electron microscopic studies of 14 cases of collagenous colitis are reported. Comparative electron microscopic examinations were carried out on 13 cases of ulcerative colitis in the chronic fibrotic stage of the disease. Separation of pericryptal fibroblasts which showed enhanced fibre-forming activity, proliferation of myofibroblasts, accumulation of mast cells and a pericapillary collagen accumulation were noted in both groups. Based on these results, collagenous colitis was considered to result fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
8
0

Year Published

1989
1989
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 19 publications
1
8
0
Order By: Relevance
“…Although neutrophils do not dominate the inflammatory infiltrates, they are seen in patients microscopic colitis, with active cryptitis found in 30% to 40% of patients. 82 Some studies have noted mast cells in the inflammatory infiltrate 52,86,87 or embedded within the collagen layer, 88 but other studies showed no difference in the numbers compared with those in control subjects. 89 The inflammatory changes are often accompanied by surface epithelial damage or even detachment 13,41 (Fig.…”
Section: Histopathologymentioning
confidence: 98%
See 3 more Smart Citations
“…Although neutrophils do not dominate the inflammatory infiltrates, they are seen in patients microscopic colitis, with active cryptitis found in 30% to 40% of patients. 82 Some studies have noted mast cells in the inflammatory infiltrate 52,86,87 or embedded within the collagen layer, 88 but other studies showed no difference in the numbers compared with those in control subjects. 89 The inflammatory changes are often accompanied by surface epithelial damage or even detachment 13,41 (Fig.…”
Section: Histopathologymentioning
confidence: 98%
“…2), often with entrapped blood cells and a ragged inferior edge, ranging from 7 to 80 μm, compared with 5 to 7 μm normally. 11,22,41,87 The basement membrane is normal, 88,89 although the collagen band is closely associated with it. 87,89…”
Section: Histopathologymentioning
confidence: 99%
See 2 more Smart Citations
“…Evidence shows, however, that "autoimmune phenomena" and an abnormal immune response to luminal antigens are involved. 11 In experimental models CD4+/CD25+ regulatory T cells (Tregs) play a critical role in the maintenance of self-tolerance, control of autoimmune diseases, and transplant rejection and have been suggested as a therapeutic option in severe inflammatory colitis. [12][13][14] It has been known for more than 5 years that CD8+ T lymphocytes (CTLs) secrete interleukin (IL) 2, which stimulates Upon completion of this activity you will be able to: • define the 2 major types of microscopic colitis, their clinical symptoms, and their microscopic characteristics.…”
mentioning
confidence: 99%